Frecuencia de paramphistomum cervi y fasciola hepática en fincas de producción bovina del municipio de Supatá, Cundinamarca - Beltrán Alba, Absalón Stwar; Vinasco Suárez, Jessica Katherine (Universidad Antonio Nariño, 2021)
Fasciolosis and Paramfistomosis in bovines produces great economic losses in livestock farms all over the world, especially in tropical countries. These losses include the decrease in the weight gain of the animals, losses in milk production, reproductive problems, seizures of livers and other organs at the slaughterhouse level, discarding of chronically affected animals, added to the high costs for treatments. and control measures. The present work evaluated the percentage frequency, the presence of clinical signs related to Paramphistomum cervi and Fasciola hepatica, as well as identifying the risk factors associated with the presence of intermediate host molluscs in bovine production farms in the municipality of Supata, Cundinamarca. The modified Happich-Boray technique (Sedimentation and Sieving) was used, with results in the frequency of Paramphistomum cervi and Fasciola hepatica, in cattle in the municipality of Supatá, which was 49% and 29% respectively. The environmental and topographic conditions are favorable for the development of the intermediate host, regardless of the climatic season, as it is an area of high humidity. Adult cows during the lactation period were the most affected group, especially those of the Holstein breed, showing a higher susceptibility to Paramphistomum cervi and Fasciola hepatica.